Comparison of Photonic to Plasmonic Mode Converters for Plasmonic Multiple-Input Devices - Samantha Lubaba Noor; Francky Catthoor; Dennis Lin; Pol Van Dorpe; Azad Naeemi (IEEE Photonics Journal, 2024)
Implementing a compact optical integrated circuit by utilizing subwavelength plasmonic devices requires the design of compact and efficient photonic to plasmonic mode converters. Especially for plasmonic multiple-input devices such as logic gates that require multiple converters, the footprint can be largely penalized by the photonic waveguides, which should be considered in the design. In this work, we simulate and benchmark five photonic to plasmonic mode converter topologies for the application of multiple-input plasmonic devices. Our design includes both directional and end coupling schemes of plasmonic waveguide and Si photonic waveguides of wire and slot configurations. We optimize the performance of the converters considering the pitch mismatch between the photonic and plasmonic waveguides, the total footprint, and mode conversion efficiency.